1925 Or. Gen. and Special Laws 469-70, ch. 260, § 5 - (:unkn) unknown (My University, 1925)
it shall be unlawful for any person within this state to carry concealed upon his person or within any vehicle which is under his control or direction any pistol, revolver or other firearm capable of being concealed upon the person without having a license to carry such firearm, as hereinafter provided in section 8 hereof
Keywords: CARRY - CONCEALED